A cross-sectional study of socio-demographic and clinical profile of HIV patients at ART plus centre, Sawai Man Singh Hospital, Jaipur, India (Journal of Ideas in Health, 2021)
Background: This study aimed to understand the regional variation in the socio-demographic and clinical profile of human immunodeficiency virus (HIV) infected patients at antiretroviral therapy plus centre of Sawai Man Singh (SMS) hospital, Jaipur, India. Methods: A descriptive cross-sectional study was conducted on HIV patients from January to December 2019. The HIV-positive patients of all age groups and all categories were included in the study. The socio-economic status was assessed by BG Prasad classification-based consumer price index. However, the clinical staging was done according to the World Health Organization (WHO) classification of HIV/AIDS. Data were expressed as mean ± standard deviation.Results: Among 525 HIV patients 59.16% were males, 40.26% females and 0.57% intersex. About half (51.0%) in the reproductive age group with mean age 36 ±13 years. The commonest mode of HIV transmission was heterosexual (89.77%). Maximum belonged to social class I (57.84%) and class II (26.05 %) of BG Prasad's socioeconomic status. Each of the non-agricultural laborers and semi-skilled workers constitutes 18.0%, and the housewives were 23.6%. At the time of presentation, baseline CD4+Tcell count was
Keywords: Clinical Profile HIV, Socio-demographic Profile HIV, Opportunistic Infection, Antiretroviral Therapy, India